Impact of Bracing on Large Format Prismatic Lithium‐Ion Battery Cells during Aging. Issue 10 (4th December 2021) - Daubinger, Philip; Schelter, Matthias; Petersohn, Ronny; Nagler, Felix; Hartmann, Sarah; Herrmann, Matthias; Giffin, Guinevere A.
Abstract: To reduce the ecological footprint and to increase the lifetime of lithium‐ion batteries (LIBs), it is necessary to understand aging phenomena inside the cells during cycling. In this study, the positive effect of external pressure through bracing the cells on aging is investigated for automotive battery cells with more than 7000 cycles. After cycling, the aged cells are studied by using post‐mortem analysis. It is shown that bracing does not affect the anode and cathode in the same manner. A lack of external pressure results in lithium plating due to contact losses on the anode. Such a loss of lithium inventory plays only a small role in the braced cells. However, the structural and morphological degradation, such as particle cracking at the cathode, is significant. Half‐cell tests of aged and unaged anode samples extracted from the automotive cells confirm the post‐mortem findings, where only minimal differences can be seen for the braced cell. In contrast, the aged cathodes from braced cells demonstrate substantial capacity fade in half‐cell measurements as compared to the cathodes extracted from the unbraced cell. Finally, a new concept of the mechanical state of health (mechanical SOH) is introduced to correlate mechanical effects with electrode degradation. Abstract : Cycling of large format prismatic lithium‐ion cells shows that external bracing reduces aging phenomena. Although significant structural degradation of the cathode occurs, the overall impact on the cell is minor. Lithium plating along with the loss of lithium inventory are the main sources of aging in the unbraced cells.